Gender differences in long-term mortality in ischemic heart disease: results from a prospective all-comers percutaneous coronary intervention registry in Romania - Rotari Adina-Ioana; Călburean Paul-Adrian; Mesaroş Petru; Scurtu Anda-Cristina; Câmpean Ioana; Grebenişan Paul; Druică Elena; Hadadi László (Romanian Journal of Cardiology)
Although coronary artery disease (CAD) remains the leading cause of death worldwide, patient-level data on long-term outcomes in Eastern Europe are limited, particularly in Romania, where high poverty rates and low gender equality persist. This study aimed to identify sex-based differences in long-term survival after percutaneous coronary intervention (PCI) in a prospective Romanian registry of PCI procedures.